2023
DOI: 10.1055/s-0043-57009
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Monitoring with Rotational Thromboelastometry in a Severe Hemophilia A Patient Undergoing Elective Ankle Surgery

Abstract: Letter to the EditorThis document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This was emphasised by a German survey which showed that 86% of adults and 66% of children and adolescents experienced episodes of pain [ 3 ]. In addition to episodes of bleeding-related pain, PwH also experience pain associated with inflammation and multiarticular joint degeneration, with non-reversible end-stage haemophilic arthropathy [ 4 ]. Therefore, haemophilia can be considered as a chronic musculoskeletal disorder.…”
Section: Introductionmentioning
confidence: 99%
“…This was emphasised by a German survey which showed that 86% of adults and 66% of children and adolescents experienced episodes of pain [ 3 ]. In addition to episodes of bleeding-related pain, PwH also experience pain associated with inflammation and multiarticular joint degeneration, with non-reversible end-stage haemophilic arthropathy [ 4 ]. Therefore, haemophilia can be considered as a chronic musculoskeletal disorder.…”
Section: Introductionmentioning
confidence: 99%